Faktor Risiko Pneumonia Komplikata Pada Anak - Pratista Oktafia; Prananda Surya Airlangga; Ira Dharmawati; Retno Asih Setyoningrum (Majalah Kedokteran Indonesia, 2021)
Introduction: Pneumonia causes morbidity and mortality in children worldwide. Pediatric patients with complicated pneumonia have a poor prognosis and are more at risk of death. Objective To identify risk factors for complications in pediatric patients with pneumonia. Method: This research was a case-control study, involving children with pneumonia aged 1-59 months in Dr. Soetomo in 2016-2020. The sample was divided into two groups. Patients who had complications at first admission were classified as a case group. Whereas patients without complications at first admission were classified as a control group. Samples for the case group were obtained by using total sampling method, while the control group employed random sampling technique. Data were collected from medical records and analyzed by chi-square test. Result: A total of 44 case group samples and 53 control group samples were involved during this study. Among investigated variables, male gender (OR=2,842; 95% CI, 1,24-6,49) and anemia (OR=3,283; 95% CI, 1,26-8,49) might increase the risk of complicated pneumonia. Meanwhile other variables, namely age, comorbidities, birth weight, malnutrition, and immunization status did not have a significant relationship with the incidence of complications in pneumonia patients. Conclusion: Male gender and anemia are risk of complicated pneumonia.